High-Grade Endometrial Stromal Sarcoma: Molecular Alterations and Potential Immunotherapeutic Strategies - Kim, Youngah; Kim, Dohyang; Sung, Woo Jung; Hong, Jaewoo (Frontiers in Immunology, 2022)
Endometrial stromal tumors (ESTs) are rare, unusual uterine mesenchymal tumors with variegated histopathological, immunohistochemical and molecular characteristics. The morphology of ESTs is similar to normal endometrial stromal cells in the proliferative phase of the menstrual cycle. EST was first classified into benign and malignant according to the count of mitotic cells. But recently, WHO divided ESTs into four categories, which are endometrial stromal nodule (ESN), low-grade endometrial stromal sarcoma (LG-ESS), high-grade endometrial stromal sarcoma (HG-ESS), and undifferentiated uterine sarcoma (UUS). HG-ESS is highly malignant among these categories with poorer clinical outcomes compared to other types. As molecular biology advanced, EST has been categorized more in detail with morphological identification. ESTs, including HG-ESS, is a relatively rare type of cancer, and the therapeutics are not being developed compared to other cancers. However, considering the tumor microenvironment of usual stromal cancers, the advance of immunotherapy shows auspicious outcomes reported in many different stromal tumors and non-identified uterine cancers. These studies show the high possibility of successful immunotherapy in HG-ESS patients in the future.